Beach vibes - Mallery, Susan (Canary Street Press, 2025)
While Beth is proud of her Malibu beach shop, Surf Sandwiches, she's even prouder of her charismatic brother Rick, who rose from foster care through surgical residency. She makes subs, he saves lives. Life takes a turn for the happy after she finds out Rick is dating her new best friend, Jana. Then Jana's handsome brother adds even more sparkle to Beth's days... and nights. But when she catches Rick with another woman--like, with-with--her visions of an idyllic family future disappear in one awful instant. Either she betrays her brother, or she keeps his secret and risks losing the man she loves and her best friend.